Permanent distortion : how the financial markets abandoned the real economy forever - Prins, Nomi (PublicAffairs, 2022)
"The 21st century has produced two major financial crises and many smaller ones in between. The fallout created chaos and disruption for people at all levels of the global economy. Nomi Prins examines the consequences of the unstable economy that caused what she calls the state of Permanent Distortion; a wedge between a funhouse financial realm that thrives even in times of social and political disorder, and a struggling economic one that does not adequately meet the needs of the general population. Through deep reporting and insightful analysis, Prins navigates the critical points in between the two polarities, including how the concept of "free markets" is dead, how a political power shift is bringing in a new world order, why trade wars have only just begun, and why we're in for more civil and social unrest, as a result"--